Case Report A Rare Case of Geleophysic Dysplasia: Clinical and Radiological Insights: A Rare Case of Geleophysic Dysplasia (Bombay Hospital Journal, 2026)
BackgroundGeleophysic dysplasia (GD) is predominantly a disorder of the musculoskeletal system which also affects the skeletal, cardiovascular, respiratory, otologic, and ophthalmologic systems. A suspicion of GD can arise right from the abnormalities in the obstetric scans of the patients. Further, the diagnostic workup encompasses of a primary skeletal survey, MRI of brain and spine for suspected neurologic problems, 2D echocardiography for congenital heart defects and genetic study. Retrospectively, workup of the parents is also necessary. The management is a multimodality approach with regular visits with a pediatrician who overall monitors the child, an orthopedic surgeon and other specialties depending on the involvement of other systems.Case DescriptionThe case described by us is a one-month old neonate who had fetal growth restriction and scalloping of the skull bones on obstetric scans. On further workup, the spinal cord was low tethered showing type II diastematomyelia. Multiple cardiac defects were also present along with bilateral cryptorchidism.Clinical SignificanceThis case showcases an autosomal recessive variant of GD in a neonate, emphasizing its multisystemic features, diagnosis, and multidisciplinary management. Neurological involvement which is not usually seen in GD, was encountered in our case.KEYWORDS: Neural tube defects, Heart defects Congenital, Skeletal dysplasia.
Keywords: Neural tube defects; Heart defects Congenital; Skeletal dysplasia